Update Breast Cancer 2019 Part 2 – Implementation of Novel Diagnostics and Therapeutics in Advanced Breast Cancer Patients in Clinical Practice - Janni, Wolfgang; Schneeweiss, Andreas; Müller, Volkmar; Wöckel, Achim; Lux, Michael P.; Hartkopf, Andreas D.; Nabieva, Naiba; Taran, Florin-Andrei; Tesch, Hans; Overkamp, Friedrich; Lüftner, Diana; Belleville, Erik; Schütz, Florian; Fasching, Peter A.; Fehm, Tanja N.; Kolberg, Hans-Christian; Ettl, Johannes (Geburtshilfe und Frauenheilkunde, 2019)
The treatment of patients with advanced breast cancer has developed further in recent years. In addition to therapeutic progress in the established subgroups (hormone receptor and HER2 status), there are now therapies which are geared to individual molecular characteristics, such as PARP inhibitor therapy in BRCA-mutated patients. In addition to this, tests are being developed which are intended to establish additional markers within subgroups in order to predict the efficacy of a therapy. PI3K mutation testing in HER2-negative, hormone-receptor-positive tumours and PD-L1 testing of immune cells in triple-negative tumours are expected to become established in clinical practice in order to select patients for the respective therapies. With new therapeutic approaches, new adverse effects also appear. The management of these adverse effects, just as those of classical therapy (supportive therapy), is essential with the introduction of new treatments in order to preserve patientsʼ quality of life. Knowledge regarding measures to preserve and improve quality of life has significantly increased in recent years. Lifestyle factors should be taken into account, as should modern therapeutic methods. This review summarises the latest studies and publications and evaluates them in regard to the relevance for clinical practice.Die Behandlung von Patientinnen mit fortgeschrittenem Mammakarzinom hat sich in den letzten Jahren weiterentwickelt. Zusätzlich zum Therapiefortschritt in den etablierten Subgruppen (Hormonrezeptor- und HER2-Status) gibt es nun Therapien, die sich an einzelnen molekularen Charakteristika orientieren, wie zum Beispiel die PARP-Inhibitortherapie bei BRCA-mutierten Patientinnen. Zusätzlich dazu sind Tests in der Entwicklung, die innerhalb von Subgruppen weitere Marker etablieren sollen, um die Wirksamkeit einer Therapie vorherzusagen. Die PI3K-Mutationstestung bei HER2-negativen, hormonrezeptorpositiven Tumoren, und die PD-L1-Testung von Immunzellen bei triple-negativen Tumoren werden voraussichtlich in der klinischen Praxis etabliert, um Patientinnen für die jeweiligen Therapien auszuwählen. Mit neuen Therapieansätzen treten auch neue Nebenwirkungen auf. Das Management dieser Nebenwirkungen ebenso wie die der klassischen Therapien (supportive Therapie) ist mit der Einführung neuer Behandlungen essenziell, um die Lebensqualität der Patientinnen zu erhalten. Das Wissen über Maßnahmen zur Erhaltung und Verbesserung der Lebensqualität hat in den letzten Jahren deutlich zugenommen. Lifestyle-Faktoren sollten dabei ebenso Berücksichtigung finden wie moderne Therapieverfahren. Diese Übersichtsarbeit fasst die neuesten Studien und Veröffentlichungen zusammen und bewertet sie in Bezug auf die Relevanz für die klinische Praxis.
Keywords: breast cancer; metastatic; advanced; PI3K; PD-L1; alpelisib; atezolizumab; PARP; supportive therapy